Nutritional composition and aerobic stability of winter cereal silage at different storage times - Guilherme Fernando Mattos Leão; Cloves Cabreira Jobim; Mikael Neumann; Egon Henrique Horst; Sthefany Kamile dos Santos; Bruno José Venancio; Leslei Caroline Santos (Acta Scientiarum. Animal Sciences, 2017)
The objective of the experiment was to evaluate the nutritional composition, dry matter (DM) recovery and aerobic stability of winter cereal silages under different storage periods. The materials used were wheat (Triticum aestivum cv. BRS Gralha Azul), barley (Hordeum vulgare cv. BRS Brau), white oat (Avena sativa cv. URS Guará), black oat (Avena strigosa cv. Embrapa 139) and triticale (X Triticosecale IPR 11), in three storage periods: 60, 120 and 180 days. The experiment was conducted in a 5x3 factorial, completely randomized design, consisting of five forage species and three storage periods, with five replicates. In nutritional assessment, barley silage presented low values of acid detergent fiber (ADF; 331.2, 355.2 and 378.5 g kg DM-1 for 60, 120, 180 days, respectively), high total digestible nutrients (TDN; 558.2, 544.7 and 531.6 g kg DM-1 for 60, 120, 180 days, respectively), high DM recovery and aerobic stability. Wheat and triticale showed a decrease in DM recovery with the increase in storage length, although showed high aerobic stability. The storage period had a different effect on forages; however, storage period above 60 days provided no benefits for the variables evaluated.